The Relationship between Attitudes toward Suicide and Family History of Suicide in Nagano Prefecture, Japan - Tsukahara, Teruomi (Int J Environ Res Public Health, 2016)
Certain attitudes toward suicide may be a risk factor for suicide among the bereaved. To explore this possibility, we examined the relationship between attitudes toward suicide and family history of suicide. We focused on two specific attitudes indicating resignation in a survey: #1 “When a person chooses to die by suicide, the suicide is inevitable” (i.e., inevitability belief); and #2 “A suicide cannot be stopped by any person, because suicide is unpreventable” (i.e., unpreventable belief). The data of 5117 fully completed questionnaires were analyzed. Logistic regression analysis revealed that the two attitudes of resignation were significantly associated with a family history of suicide. The adjusted odds ratio for #1 was 1.39 (95% CI, 1.07–1.79) for individuals having experienced suicide by a family member or relative, while that for #2 was 1.57 (95% CI, 1.27–1.95) for experiencing a suicide by a family member or relative and 1.25 (95% CI, 1.05–1.49) for experiencing a suicide by a friend, business associate, partner or other. These two attitudes of resignation toward suicide were significantly associated with a family history of suicide. These attitudes might increase suicide risk among the bereaved.